Representations of war, migration, and refugeehood interdisciplinary perspectives - Rellstab, Daniel H. 1972-; Schlote, Christiane (Routledge, Taylor & Francis Group, 2019)
"War, migration, and refugeehood are inextricably linked and the complex nature of all three phenomena offers profound opportunities for representation and misrepresentation. This volume brings together international contributors and practitioners from a wide range of fields, practices, and backgrounds to explore and problematize textual and visual inscriptions of war and migration in the arts, the media, and in academic, public, and political discourses.The essays in this collection address the academic and political interest in representations of the migrant and the refugee, and examine the constructed nature of categories and concepts such as 'war,' 'refuge(e),' 'victim,' 'border,' 'home,' 'non-place,' and 'dis/location.' Contributing authors engage with some of the most pressing questions surrounding war, migration, and refugeehood as well as with our own responses to the ways in which war and its multifarious effects and repercussions in society are being framed, propagated, glorified, or contested.This volume initiates an interdisciplinary debate which re-evaluates the relationship between war, migration, and refugeehood and their representations"--
Keywords: Massenmedien; Flüchtling -- Motiv; Künste; Krieg -- Motiv; Literatur; Migration -- Motiv; Aufsatzsammlung